Comportamento omissivo e colisão de deveres em direito penal - Gonçalves, Lucas Minorelli (2016)
The object of analysis of this scientific research is the problem of the collision of duties in criminal law and the main purpose was to investigate the legal-penal treatment given to such cases. The methodology consists n the bibliographic review and analysis of legal precedents related to the thematic, with the analysis of the proposals of resolution to the problem. The present work is structured in three chapters. In the first chapter, it seeks to recover the dogmatic, legislative and jurisprudential antecedents of five countries (Germany, Italy, Spain, Portugal and Brazil). On the other hand, in the second chapter analyses the main proposals of resolution of collision of duties, which were gathered in nine groups (causes of reduction of the penalty, exclusion of the penalty, exclusion of mens rea, abstaining from the judgment of guilt, exclusion from the responsibility of the fact, justification, theory of free space of law and cause of exclusion of actus reus), analyzing the merits and demerits of each theoretical construction. In the third and final chapter there is the taking of a position on the subject, in which it is concluded that the collision of duties, despite having few similarities with the necessity, has its application restricted to collisions between duties of action, having its own a foundation and legal consequences, and it is the sole cause of justification in cases involving innocent lives.